GINÁSTICA ARTÍSTICA: DESEMPENHO DOS ATLETAS DA CATEGORIA ‘‘A” NO CAMPEONATO ESCOLAR GAÚCHO NO ANO DE 2009 - Fernandes, Raone B.; Taborda, Douglas d. S.; Gherke, Carolina; Filho, Leopoldo S. (Salão do Conhecimento, 2013)
Resumo